Relationship between thrombolysis efficiency induced by pulsed focused ultrasound and cavitation bubble size. (November 2015) - Xu, S; Liu, X; Wang, S; Wan, M
Abstract: In this study, the relationship between the efficiency of pulsed focused ultrasound (FUS)-induced thrombolysis and the size distribution of cavitation bubbles has been studied. Firstly, the thrombolysis efficiency, evaluated by degree of mechanical fragmentation was investigated with varying duty cycle. Secondly, the size distribution of cavitation bubbles after the 1st, 10 3 th and 10 5 th pulse during experiments for various duty cycles was studied. It was revealed that the thrombolysis efficiency was highest when the cavitation bubble size distribution was centred around linear resonance radius of the emission frequency of the FUS transducer. Therefore, in cavitation enhanced therapeutic applications, the essential of using a pulsed FUS may be controlling the size distribution of cavitation nuclei within an active size range so as to increase the treatment efficiency.